International Reserve Adequacy in Central America - Magnussen, Kristin (IMF Working Papers; Working Paper ;, 2011)
Countries' absolute and relative international reserves adequacy has recently attracted considerable attention. The analysis has however concentrated on the largest and most advanced economies. We apply various methodologies for assessing reserve adequacy in Central America, taking into account the region's high degree of deposit dollarization. We find that reserve cover is low both in an absolute and relative sense, suggesting further reserve accumulation is an important policy option for reducing vulnerabilities.